2006
DOI: 10.1097/01.ccm.0000215457.83953.e3
|View full text |Cite
|
Sign up to set email alerts
|

Insulin reduces the multiple organ injury and dysfunction caused by coadministration of lipopolysaccharide and peptidoglycan independently of blood glucose: Role of glycogen synthase kinase-3β inhibition*

Abstract: Therapy with insulin or the potent and selective glycogen synthase kinase-3beta inhibitor TDZD-8 reduced the organ injury/dysfunction caused by lipopolysaccharide and peptidoglycan in the rat. We propose that the inhibitory effect of insulin on the activity of glycogen synthase kinase-3beta contributes to the protective effect of insulin against the organ injury/dysfunction caused by excessive systemic inflammation independently of any effects on blood glucose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 42 publications
1
47
0
1
Order By: Relevance
“…For instance, insulin has been shown to increase the expression of mitogen-activated protein kinase phosphatase (MKP-1) in a PI3K-dependent manner (Desbois-Mouthon et al, 2000;Takehara et al, 2000), and this phosphatase negatively regulates IL-6 and TNF-␣ production in endotoxemic mice (Chi et al, 2006). Furthermore, a recent study showed that insulin and a glycogen synthase kinase 3␤ inhibitor had similar anti-inflammatory effects in a rat model of sepsis (Dugo et al, 2006). It is noteworthy that Akt-dependent phosphorylation decreases the activity of glycogen synthase kinase 3␤ (Guha and Mackman, 2002;Martin et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, insulin has been shown to increase the expression of mitogen-activated protein kinase phosphatase (MKP-1) in a PI3K-dependent manner (Desbois-Mouthon et al, 2000;Takehara et al, 2000), and this phosphatase negatively regulates IL-6 and TNF-␣ production in endotoxemic mice (Chi et al, 2006). Furthermore, a recent study showed that insulin and a glycogen synthase kinase 3␤ inhibitor had similar anti-inflammatory effects in a rat model of sepsis (Dugo et al, 2006). It is noteworthy that Akt-dependent phosphorylation decreases the activity of glycogen synthase kinase 3␤ (Guha and Mackman, 2002;Martin et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…23,24 To date, TDZD-8 has been evaluated primarily as a cytoprotective agent in multiple rodent models for maladies such as septic and nonseptic shock, lung injury, arthritis, spinal cord injury, colitis, and Alzheimer disease. [25][26][27][28][29][30][31][32][33] However, in the present study we describe an entirely new activity for TDZD-8, which thus far appears to be restricted to cells derived from hematologic malignancies. We show that this compound is strongly cytotoxic to multiple types of primary leukemia cells, as well as phenotypically and functionally defined LSCs.…”
Section: Introductionmentioning
confidence: 87%
“…In addition, the reduction of endotoxin and peptidoglycan-induced pathologic conditions in rats by insulin, independent of blood glucose changes, has been demonstrated to involve GSK-3 inhibition (Dugo et al, 2006). Others reported that the insulin resistance and associated increase in GSK-3␤ activity in brains of a mouse model of T2DM, as well as what the authors noted were learning difficulties parallel to those seen in AD, were corrected by administering insulin (Jolivalt et al, 2008).…”
mentioning
confidence: 88%